Non‐human primates: the appropriate subjects of biomedical research? - Quigley, Muireann (BMJ Group, 2007)
Following the publication of the Weatherall report on the use of non‐human primates in research, this paper reflects on how to provide appropriate and ethical models for research beneficial to humankind. Two of the main justifications for the use of non‐human primates in biomedical research are analysed. These are the “least‐harm/greatest‐good” argument and the “capacity” argument. This paper argues that these are equally applicable when considering whether humans are appropriate subjects of biomedical research.